Historical Transformations of Ukrainian Ritual Culture in an Urban Environment (1920s – Early Twenty-First Century) - Bekh, K. (Український історичний журнал, 2021)
The aim of the article is analyzing and elucidating the main transformations and changes in the
components of the Ukrainian ritual culture in urbanized environment. The research methodology is based
on general scientific (analysis, synthesis, generalization), special (comparative historical, problem-chronological),
source study methods, as well as the method of direct observation. The scientific novelty consists in
analyzing significant modifications and revealing the trends in components’ transformation of the traditional
Ukrainians’ culture in urbanized environment. It has been mentioned, that peculiar attention has to be
paid to the city as a center of culture, which constantly develops; here spiritual value and ethnical orientations
of city dwellers are formed and synthesized. First of all, attention was paid to the development, existence and
modification of family rituality and its marriage and wedding component as one of the most important ethnic
identification indicators and the element of ethnicity preservation. The main factors of transformational
ritual practices and decreasing the traditional rituality components during different periods of social, political
and globalization processes were elucidated. The main results and conclusions. It has been noted that
during the 1920s – 1980s the Soviet power played considerable role in the transformation of spiritual foundations
of the Ukrainian people. In particular, the creation of a new family was socially significant and it was
under the state authorities’ control, which was especially manifested in cities. During the mentioned period,
the standardization and unification of the ritual wedding ceremony took place, which considerably affected
the loss of many of its components, considerably narrowing its national color, high esthetics of song culture
and theatrical performances. Instead, the end of the 20 – early of the 21 centuries is characterized by intensive
globalization. It has been determined that wide using of innovative technical means of communication as
one of the important factors caused significant transformations of the Ukrainians’ ethnic culture. Modern
family rituality of city dwellers, marriage-wedding, in particular, on the one hand, is characterized by variability
and diversity, and on the other hand, by reactivation of traditional rites, phenomena, and attributes. Метою статті є аналіз та висвітлення основних трансформацій і видозмін компонентів української обрядової культури в урбанізованому середовищі. Методологія дослідження базується на загальнонаукових (аналіз, синтез, узагальнення), спеціальних (порівняльно-історичний, проблемно-хронологічний), джерелознавчих методах, а також використано метод
безпосереднього спостереження. Наукова новизна полягає в аналізі знакових видозмін та
виявленні тенденцій трансформації компонентів традиційної культури українців в урбанізованому середовищі. Відзначено, що особливої уваги потребує місто – осередок культури, який
перебуває в постійному процесі розвитку, тут формуються й синтезуються духовно-ціннісні й
етнічні орієнтації містян. Увагу приділено насамперед розвитку, побутуванню та модифікації
сімейної обрядовості і її шлюбно-весільної складової, як одного з найважливіших етноідентифікаційних показників та елемента консервування етнічності. Висвітлено основні чинники
трансформаційних обрядових практик та скорочення традиційних компонентів обрядовості у
різні періоди суспільно-політичних і глобалізаційних процесів. Основні результати й висновки. Відзначено, що протягом 1920–1980-х рр. радянська влада відіграла значну роль у трансформації духовних основ українського народу. Зокрема створення нової сім’ї мало суспільне
значення, перебувало під контролем державних органів, що особливо проявилося в містах.
У вказаний період відбувається стандартизація та уніфікація ритуально-обрядової складової
весілля, що значною мірою вплинуло на втрату багатьох його компонентів, істотно звузивши
його національний колорит, високу естетику пісенної культури та театралізованих дійств. Натомість кінець ХХ – початок ХХІ ст. характеризується інтенсивною глобалізацією. Визначено,
що широке використання інноваційних технічних засобів комунікації, як одного з вагомих чинників, суттєво спричиняє трансформації етнокультури українців. Сучасна сімейна обрядовість міського населення, зокрема шлюбно-весільна, з однієї сторони характеризується варіативністю та строкатістю, а з іншої – реактивацією традиційних ритуалів, явищ, атрибутів.